(untitled) (Journal of the College of Basic Education, 2024)
The thesis contains five chapters: The first chapter included the introduction, the importance of the research, and the research objective 1- Preparing an educational design according to the Kemp model of motor abilities and learning the offensive skills of basketball for students. 2- Knowing the effect of educational design according to the Kemp model on the motor abilities and learning the offensive skills of basketball for students. The second chapter included the theoretical framework and interrelated studies. The third chapter included the research methodology and its field procedures, and the researcher used the experimental method, and the research community reached (132) students from the first stage in the Department of Physical Education and Sports Sciences - University College of Peace for the academic year 2021/2022, with a rate of (4) people, As for the research sample, it was chosen by the systematic random method, as two divisions were chosen from the original research community, namely Division (A-D) and by lottery Division (A) numbering (34) students became an experimental group and Division (D) whose number was (33) students A control group, and (7) students were excluded from the two divisions, as the number of excluded students were (4) students from Division (A), and (3) female students from Division (D), and the research sample became (60) students distributed equally among the two groups. The exploratory experiment was conducted on a sample of (10) students who are students of Division (C), and the percentage of the sample amounted to (46.15%) from the community of origin. As the experimental group has applied the educational units in a triple peer learning method according to the learning stations and visual vision exercises in learning some types of basketball scoring, and it reached (8) educational units. By two units per week, the time of the educational unit is (90) minutes. The fourth chapter included presentation, analysis and discussion of the results, and included a detailed presentation of the results of all tests. The fifth chapter included the conclusions, namely: - The researcher concluded that the experimental group on which the Kemp model was applied was superior to the control group that applied the curriculum followed by the subject teacher in improving the motor abilities and offensive skills of basketball for students. The researcher recommends emphasizing the use of the KMP model in recent studies and practical lessons, and choosing exercises that are appropriate with students and the game.